Research on the Synergistic Mechanism of Maize–Soybean Rotation and Bio-Organic Fertiliser in Cold Regions - Zijian Wang; Hao Tian; Nan Sun; Haocheng Wang; Songyan Tang; Shengjie Chen; Xuebing Wang; Shiwei Ren; Xiangyuan Zuo; Xingbo Zhao (Agronomy)
Aiming to address a series of problems caused by inefficient nitrogen fixation in soybean within the maize–soybean rotation system under cold-region conditions in Heilongjiang Province, China—such as reduced crop yields, declining soil fertility, and increased dependence on chemical fertilisers—this study investigated the partial substitution of chemical nitrogen fertilisers with bio-organic fertilisers at replacement rates of 10%, 20%, and 30% during soybean cultivation. The treatments included bio-organic fertilisers (OB1, OB2, OB3), inactivated bio-organic fertilisers (O1, O2, O3), Bacillus subtilis (B1, B2, B3), and a control (CK) with the conventional application of chemical fertilisers. In the rotational maize cropping phase, a 50% nitrogen reduction was applied. The results showed that replacing 20% of soybean nitrogen fertiliser with bio-organic fertiliser (OB2 treatment) yielded the most significant increase in productivity and economic return. Compared with CK, the OB2 treatment increased soybean yield by 26.56%, maize yield by 26.69%, and nitrogen fertiliser use efficiency by 3–5%. According to the GRA-TOPSIS model, the OB2 treatment demonstrated the greatest capacity to improve quality and efficiency in the maize–soybean rotation system. At the soybean maturity stage, the OB2 treatment increased soil total organic carbon, available phosphorus, and soil protease activity by 25.36%, 22.20%, and 87.50%, respectively, compared with CK. At maize maturity, soil ammonium nitrogen and soil protease activity increased by 80.24% and 62.47%, respectively. Bio-organic fertilisers combine the benefits of organic fertiliser substrates with those of functional microorganisms. Correlation, cluster, and interaction analyses revealed that the synergistic mechanisms between maize–soybean rotation and bio-organic fertilisers in cold regions are primarily reflected in improved soil quality, enhanced nutrient cycling efficiency, increased nitrogen fixation in soybean root nodules, stimulated microbial activity, and greater resilience to environmental stress. Sustainable agricultural production in cold regions can be achieved through the integrated functioning of these system components. This study provides a theoretical basis for enhancing yield and efficiency in maize–soybean rotation systems under cold climatic conditions.